Combined scanning small‐angle X‐ray scattering and holography probes multiple length scales in cell nuclei. (21st January 2021) - Wittmeier, Andrew; Cassini, Chiara; Töpperwien, Mareike; Denz, Manuela; Hagemann, Johannes; Osterhoff, Markus; Salditt, Tim; Köster, Sarah
Abstract : The combination of small‐angle X‐ray scattering and X‐ray holography enables us to visualize and characterize biological material in cell nuclei spanning multiple length scales. Abstract : X‐rays are emerging as a complementary probe to visible‐light photons and electrons for imaging biological cells. By exploiting their small wavelength and high penetration depth, it is possible to image whole, intact cells and resolve subcellular structures at nanometer resolution. A variety of X‐ray methods for cell imaging have been devised for probing different properties of biological matter, opening up various opportunities for fully exploiting different views of the same sample. Here, a combined approach is employed to study cell nuclei of NIH‐3T3 fibroblasts. Scanning small‐angle X‐ray scattering is combined with X‐ray holography to quantify length scales, aggregation state, and projected electron and mass densities of the nuclear material. Only by joining all this information is it possible to spatially localize nucleoli, heterochromatin and euchromatin, and physically characterize them. It is thus shown that for complex biological systems, like the cell nucleus, combined imaging approaches are highly valuable.